Complementarity of pain assessment instruments in children with central nervous system impairment - Betina Bittencourt; Márcia Koja Breigeiron; Fernanda da Silva Flores; Simone Silveira Pasin
ABSTRACT Objective: To evaluate the complementarity of the revised Face, Legs, Activity, Cry, Consolability scale and of the Inventory of Pain Behavior in Neurological Disability for the assessment of pain in children with severe neurological impairment. Method: Cross-sectional study conducted in pediatric units of a university hospital in the southern region of Brazil. The sample consisted of 26 children with severe neurological impairment, hospitalized from January to August 2019, and their caregivers. The data were analyzed by descriptive statistics; Kappa Coefficient, Fisher's Exact Test and Spearman's Coefficient were used (p≤0,05). Results: Most children primary diagnosis was cerebral palsy (80.8%). Pain was present in 50.0% of children with the application of the scale and in 34.6% with that of the inventory. Considering the two instruments, there was good agreement (84.6%) between respondents (k=0.692; 95% CI 0.437-0.967; p=0.000). Conclusion: The instruments can be used complementarily to assess pain in children with this profile.